Anxious phenotype potentiates damage in peripheral organs of animals submitted to sepsis - Michels, Monique; Ávila, Pricila; Michelon, Cleonice; Burger, Henrique; Sonai, beatriz; Abatti, Mariane; Bilesimo, rafaela; millioli, maria vitoria; Fucilini, vanessa; Steckert, amanda; fernandez, jesus landeira; dal-pizzol, felipe (Journal of Health & Biological Sciences, 2018)
Introduction: Anxiety and sepsis are important public health problems that present high morbidity, mortality and significant economic repercussions. The present study investigated the presence of oxidative damage in peripheral organs in two lines of animals that are bred for high and low freezing responses to contextual cues that are previously associated with foot shock (Carioca High-conditioned Freezing [CHF] and Carioca Low-conditioned Freezing [CLF]) associated to sepsis. Methods: Animals were subject to sepsis by the cecal ligation and perforation (CLP) or sham operated. 24 hours and 10 days after sepsis animals were euthanized and removed adrenal, kidney, lung, serum, heart for the determination of carbonyl protein levels and adrenal for check weight this structure. Results: Sepsis increased oxidative damage in different systemic organs, included serum. There wasn’t a significant increase in protein carbonyls in heart and kidney. Anxious phenotype potentiates this damage. Conclusion: These findings suggest that an anxious phenotype plus sepsis may induce more pronounced organs damage, and promote more alterations in the HPA axis. These findings may help to explain, at least in part, the common point of the mechanisms involved with the pathophysiology of sepsis and anxiety.